Conceptualization of the experience of the individual in the educational space in the light of scientific rationality as a problem of professional identity in global and sociocultural dynamics - V.Kuznetsov, A. (2019)
As a problem, professional identity associated with the educational space is investigated from the position of belonging to professional groups. The contradictory state of education in the modern world actualizes the problem of identity in the educational space from the perspective of classical modern European rationality with its focus on the scientific forms of cognition, knowledge. The current situation in the world educational space is developed in the ambiguity of the idea of the world, which is expressed in the crisis of universalism and cognitive integrity: the place of rational knowledge in culture is replaced by mythic ideas. The way of thinking exists independently of the individual. The transfer of thinking is a learning task. However, at the present stage, with a sharp increase in the amount of information reported, the emphasis is on formalizing of the educational process, rather than constructivizing. The teacher’s responsibility as a carrier of scientific rationality, which primarily defines the universal meaning of human activity in the transmission of social experience and knowledge, is growing. The level of education of a person is a measure of implementation of the possibility of his/her formation, taking into account the dichotomous nature of the individual's socialization and professional identity based on it. Such a holistic perception of the world will allow gaining a deep understanding of the essence of things, fitting science into the cultural context of modernity.